Insufficiently dehydrated hydrogen bonds as determinants of protein interactions - Fernandez, Ariel (2003)
The prediction of binding sites and the understanding of interfaces associated with protein complexation remains an open problem in molecular biophysics. This work shows that a crucial factor in predicting and rationalizing protein-protein interfaces can be inferred by assessing the extent of intramolecular desolvation of backbone hydrogen bonds in monomeric structures. Our statistical analysis of native structures shows that, in the majority of soluble proteins, most backbone hydrogen bonds are thoroughly wrapped intramolecularly by nonpolar groups except for a few ones. These latter underwrapped hydrogen bonds may be dramatically stabilized by removal of water. This fact implies that packing defects are "sticky" in a way that decisively contributes to determining the binding sites for proteins, as an examination of numerous complexes demonstrates.